2023
DOI: 10.1002/nop2.1813
|View full text |Cite
|
Sign up to set email alerts
|

Psychological experiences of nurses caring for patients with COVID‐19: Integrative review based on qualitative research

Abstract: Aim To analyse the literature on nurses' psychological experiences caring for COVID‐19 patients, focusing on qualitative research. Design An integrative review. Review Methods Whittemore & Knafl's approach was used. Data Sources Six databases were searched using the terms ‘nurses’, ‘psychological experiences’ and ‘COVID‐19’. Results Ten studies were selected and analysed. Five characteristics related to nurses' negative psychological experiences, four characteristics related to positive psychological experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Moreover, a comprehensive review that analyzed qualitative research on nurses' psychological experiences while caring for COVID-19 patients was conducted by Lim S et al (2023). The study identified both negative and positive psychological experiences of nurses and stressed the importance of integrated support that included psychological, social, economic, and organizational aspects to enhance nurses' mental well-being and the quality of nursing care [86] .…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Moreover, a comprehensive review that analyzed qualitative research on nurses' psychological experiences while caring for COVID-19 patients was conducted by Lim S et al (2023). The study identified both negative and positive psychological experiences of nurses and stressed the importance of integrated support that included psychological, social, economic, and organizational aspects to enhance nurses' mental well-being and the quality of nursing care [86] .…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…In consistency with the findings of the present study, Feder et al's study highlights the importance of sharing feelings of loss and mourning in cases where relatives were unable to be next to their loved ones even after death [ 34 ]. Despite the physical and emotional burden that this issue involved, nurses demonstrated high levels of empathy, professional responsibility, and dedication by standing next to the patients and their families in difficult moments [ 12 , 35 , 36 ]. To a further extent, the patients’ families appeared to have a substantial role in the nurses' well-being and satisfaction, especially when caring for terminally ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…(2) In this context, the World Health Organization (WHO) has emphasized the need to safeguard the emotional and psychological health of health workers, highlighting that nursing staff is often subject to high levels of emotional stress. (2,3) From an administrative perspective, strengthening work engagement in nursing becomes a strategic imperative. Nurses, being the largest group of professionals in the health field and who spend a great deal of time in direct patient care, play a critical role in achieving organizational goals.…”
Section: Introductionmentioning
confidence: 99%